2019
DOI: 10.1002/mnfr.201900022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High‐Sucrose Diet Accelerates Vascular Stiffness in Aged Offspring via Suppressing Cav1.2 and Contractile Phenotype of Vascular Smooth Muscle Cells

Abstract: Scope: The fetal programming in response to over-nutrition during pregnancy is involved in pathogenesis of cardiovascular diseases later in life. The authors' previous work reported that prenatal high-sucrose (HS) diet impaired functions of large-conductance Ca 2+ -activated K + channels (BK) in mesenteric arteries in the adolescent offspring rats. This study determines whether prenatal HS has a long-term impact on resistance vasculature in the aged offspring rats. Methods and results: Pregnant rats are fed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…[ 22 ] Maternal high‐sucrose diets accelerated vascular stiffness and hypo‐contractility via suppressing Cacna1c in the aged offspring mesenteric arteries. [ 23 ] Recently, we found that both whole‐cell current density and expression of Cacna1c were increased in the MA myocytes from the offspring rats exposed to PHF diets. Over‐nutrition could impair vascular functions in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Maternal high‐sucrose diets accelerated vascular stiffness and hypo‐contractility via suppressing Cacna1c in the aged offspring mesenteric arteries. [ 23 ] Recently, we found that both whole‐cell current density and expression of Cacna1c were increased in the MA myocytes from the offspring rats exposed to PHF diets. Over‐nutrition could impair vascular functions in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a population‐based cohort study with 40 years of follow‐up investigated that prenatal hyperglycemia increased rates of early onset cardiovascular diseases from childhood to early adulthood, [ 34 ] our previous data confirmed that prenatal high sucrose impaired the micro‐vascular function of adult and aged offspring. [ 7,8 ] But whether it will affect fetal vessels development is still unknown. Fetal thoracic aorta is a good model in study of fetal vascular structures and functions in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4–6 ] Our previous study demonstrated that maternal high‐sucrose diet during pregnancy could induce microvascular dysfunction in both adult and aged offspring. [ 7,8 ] However, information on whether and how vascular changes have been initiated in the fetal life exposed to prenatal high‐sucrose diet is limited. Addressing such question is certainly important for further understanding development of chronic vascular diseases in fetal origins.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant rats in CON were provided with standard food and tap water, and the HS group was fed with the same food and 20% sucrose solution from gestational day 1-21. [10,[13][14][15][16] Caesarean delivery was conducted on pregnant rats at gestational day 21, and the fetal kidneys were obtained immediately. Other pregnant rats were vaginal delivery naturally.…”
Section: Animalsmentioning
confidence: 99%
“…[13,14] Our previous study revealed that maternal high-sucrose diet altered vascular contraction in the offspring. [10,15,16] However, there has limited information on underlying mechanisms to interpret the association of prenatal high-sucrose diet with vascular diseases in renal interlobar arteries from the offspring.…”
Section: Introductionmentioning
confidence: 99%